Expectations of Tele-Yoga in Persons With Long-Term Illness: Qualitative Content Analysis - Towe Hedbom; Maria Liljeroos; Ingela Thylén; Lotti Orwelius; Tiny Jaarsma; Anna Strömberg (JMIR Publications, 2023)
BackgroundYoga is a mind-body exercise that has demonstrated its feasibility and safety even for individuals with severe long-term illness. Engaging in yoga has the potential to yield positive effects on both physical and mental well-being. Tele-yoga is a novel approach to rehabilitation in which participants practice group yoga with a live-streamed yoga instructor digitally via a tablet. This is especially beneficial for individuals who may find it difficult to leave their homes to participate in an exercise session. As part of our ongoing evaluation of the tele-yoga intervention in individuals with long-term illness, we have undertaken an exploration of participants' expectations regarding yoga in general and tele-yoga specifically. Understanding these expectations is crucial, as they can significantly impact their satisfaction with treatment and care and influence overall intervention outcomes. ObjectiveThis study aims to explore the expectations of tele-yoga among individuals with long-term illness before starting a tele-yoga intervention. MethodsThe study employed an inductive qualitative design and is part of a process evaluation within an ongoing randomized controlled trial. A total of 89 participants were interviewed before the start of the tele-yoga intervention. The interview guide encompassed questions about their general perceptions of yoga and the specific expectations they held for the upcoming tele-yoga sessions. The interviews were transcribed and analyzed using inductive qualitative content analysis. ResultsParticipants expressed their expectations for tele-yoga, focusing on the anticipated improvements in physical function and overall health. These expectations included hopes for reduced respiratory issues; relief from discomfort, aches, and pains; as well as increased physical flexibility, coordination, and overall well-being. Besides, they expected to achieve improved psychological well-being and performance; to acquire strategies to manage stress, anger, and anxiety; and to have their motivational drive strengthened and influence other activities. Participants described tele-yoga as a new and exciting technical solution that would facilitate the delivery of yoga. A few participants remained a little hesitant toward the use of technology, with some expectations based on previous experiences. When asked about expectations, some had no idea about what to expect. Participants also had varying perspectives on yoga, with some finding it mysterious and difficult to understand. Participants expressed thoughts that they found the idea of tele-yoga taking place in groups exciting and enjoyable. They also had expectations that being part of a group would provide opportunities for mutual inspiration and encouragement among the group members. ConclusionsExpectations before an intervention can provide valuable insights into understanding the factors influencing adherence to tele-yoga and its outcomes. Our findings provide a wide range of expectations for tele-yoga, spanning both physical and mental aspects. Moreover, the technology's potential to facilitate yoga delivery and the supportive nature of digital group interactions were evident from the results. Trial RegistrationClinicalTrials.gov NCT03703609; https://clinicaltrials.gov/ct2/show/NCT03703609